2013
DOI: 10.3399/bjgp13x674477
|View full text |Cite
|
Sign up to set email alerts
|

Association between point-of-care CRP testing and antibiotic prescribing in respiratory tract infections: a systematic review and meta-analysis of primary care studies

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 26 publications
(103 reference statements)
1
74
1
3
Order By: Relevance
“…A normal CRP in a patient with symptoms of respiratory infection usually indicates a self-limiting infection that does not require referral to hospital or antibiotic treatment, although it may also be observed early in the presentation of an illness [29]. A systematic review and meta-analysis of 13 studies in primary care demonstrated CRP testing led to significantly reduced antibiotic prescribing at the index consultation [19]. Patient recovery without antibiotics at the same speed and with comparable rates of complications (hospitalisation, mortality, and number of re-infections), suggest that the infection was of non-bacterial origin or so mild that the immune defense could clear the infection unassisted [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A normal CRP in a patient with symptoms of respiratory infection usually indicates a self-limiting infection that does not require referral to hospital or antibiotic treatment, although it may also be observed early in the presentation of an illness [29]. A systematic review and meta-analysis of 13 studies in primary care demonstrated CRP testing led to significantly reduced antibiotic prescribing at the index consultation [19]. Patient recovery without antibiotics at the same speed and with comparable rates of complications (hospitalisation, mortality, and number of re-infections), suggest that the infection was of non-bacterial origin or so mild that the immune defense could clear the infection unassisted [30].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis that looked at 13 studies of upper respiratory tract infection (URI) and lower respiratory tract infection (LRTI) on the association between point-of-care (POC) C-reactive protein (CRP) testing and antibiotic prescribing for ARTIs in general practice found that CRP testing significantly decreased antibiotic prescribing at the initial consultation [19]. Any reduction in antibiotic consumption will have a relatively higher impact when done in a primary care setting [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Both CRP [27,28] and PCT [29,30] have demonstrated utility in differentiating bacterial from viral acute respiratory infection (ARI) in developed countries, and for PCT its use has been estimated to confer substantial economic gains (USD1.6 billion (ZAR18.8 billion) savings if used across the US health sector) in HICs. [31] In a high tuberculosis-prevalence country such as SA, the utility of CRP and PCT is less clear for ARI, as both are increased in tuberculosis.…”
Section: Antibiotic Stewardship At the Individual Patient Levelmentioning
confidence: 99%
“…A number of useful tests are now available, including CRP, which have been shown in clinical trials to reduce antibiotic prescription for respiratory tract infections. [7] Procalcitonin (PCT) is 10 times more expensive than CRP or WCC tests, but more specific for bacterial infection. There is good evidence that antibiotics can safely be withheld, based on low PCT in acute meningitis, acute exacerbations of chronic obstructive pulmonary disease and upper respiratory tract infections.…”
Section: Laboratory Testsmentioning
confidence: 99%